TURKEY WEALTH FUND AND OVERVİEW OF THE WEALTH FUNDS İN THE WORLD ECONOMY - Varış, Songül; Çiftçi, Merve; Biber, Ahmet Emre (IJRDO - Journal of Business Management, 2017)
Countries which has a wealth fund, provide a source of funds with incomes from oil, natural resources, foreign trade surplus and financial transactions. Funds have both financial stability and a global investment creature thanks to their assets. The operations and effectiveness of the wealth fund is very significant, because wealth funds are established in order to financing the large projects, reducing the effects of short – term economic shocs and fluctuations that might occur in finacial markets. Today, there are about 80 wealth funds in more than 40 countries worldwide. The total size of these funds on a global basis has reached approximately 7.4 trillion dollars. Wealth funds are formed by the intense formation of oil and natural resources, although they are established by income from exports and financial markets. In recent years, Turkey has also attended in countries that make an investment to wealth fund, which are increasing in number on a global basis. The "Turkey Wealth Fund", which was decided to be established after the July 15 coup attempt in Turkey. The Turkish Wealth Fund carries an insurance property both in terms of being a instrument for financing Turkey's future investments and for maintaining economic stabilitySources of the Turkey Wealth Fund are organizations and the decision to transfer the fund assets which in the scope and program of privatization by the High Commission for Customs, moreover It will consist of cash surplus which decided to be transferred from the Privatization Fund. Furthermore, it will also include the surplus income which is in the possession of the public sector or public institutions which are decided to be transferred to the fleet or to be managed by the company. In addition to these, the Turkey Wealth Fund will include financing and resources that are provided from domestic and foreign capital and money markets